TRIAGEM FITOQUÍMICA E ATIVIDADE ANTIOXIDANTE DE Mansoa difficilis E Hippocratea volubilis - ABEL, Mayara Cristina Neves; PEZENTI, Letícia; SILVA, Ana Francisca Gomes; FEITOSA, Bruno Henrique; FERNANDES, Nathani Alves Silva (ANAIS DO ENIC, 2018)
-